Biological characteristics on three demersal fish landed in Tegal, north coast of Central Java, Indonesia - DUTO NUGROHO; MUFTI P. PATRIA; JATNA SUPRIATNA; LUKY ADRIANTO (Society for Indonesian Biodiversity, 2016)
Nugroho D, Patria MP, Supriatna J, Andrianto L. 2016. Biological characteristics on three demersal fish landed in Tegal, north coast of Central Java, Indonesia. Biodiversitas 17: 679-686. Java Sea has a potential marine biodiversity that has been harvested since years. Demersal fish resources is one of the targeted species by Danish seine fisheries operated in North coast of Java. To support on developing conservation and management measures, an observation on species composition, length frequencies and maturity stages were carried out during August 2014 to July 2015. Sampling took place in landing place of Tegalsari fishing port central Java. A total 129 fish species identified, among them 91 species were targeted as edible fish. Sampling on three dominant species i.e., Purple-spotted bigeye Priacanthus tayenus (Richardson, 1846), Lattice monocle bream Scolopsis taenioptera (Cuvier, 1830) and goatfish Upeneus sulphureus (Cuvier, 1829) were measured regarding length, weight and their maturity stages. The results shows that length-weight relationship for each species were P. tayenus W = 0.0324 L 2.7321, S. taenioptera W = 0.0366 L2.7262 and U. sulphureus W = 0.038 L2.7312.Monthly average GSI of P. tayenus and S. taenioptera indicated that the highest index occurred during SE monsoon while U. sulphureus on NW monsoon. Maturity stage analysis indicated that estimated of length at first maturity (Lm) were at 12.9 cmFL (U. sulphureus), 16.8 cmFL (S. taenioptera) and 19.4 cmFL (P. tayenus). Size frequency distribution shows that most of the fish were caught at immature cohorts. The diversity or evenness indices of ichtyofauna is also described as descriptors of community structure and be complemented with information on biological characteristics of those dominant species.Keywords: Demersal fish, dominant species, biological characteristics, north coast, Java